Well-being of Students Affected by Disaster: A Case Study of 2004 Tsunami in Sri Lanka - Samudra Kumari Senarath (TDMRC, Universitas Syiah Kuala, 2020)
The main objective of the study was to identify the long-term well-being of students affected by the tsunami of December 2004. The specific aims of the study were to evaluate the psychological, social and educational well-being of students affected by the tsunami, 13 years after the tsunami; and to examine the nature of psycho-social counselling and material support and how these services contributed to their well-being. The methods used to gather data were both quantitative and qualitative with purposive sampling, using the class teachers’ nominations. Six school teachers and five counsellors and 43 girls and 42 boys from the Southern Province were enrolled in the study. The results of the study showed how students affected by the tsunami had to face different trauma related experiences such as their family members remaining missing and their family members’ death or injury, although the students themselves had escaped the tidal waves. Thus, the trauma related to experiences of the tsunami caused the students to have many psychological and emotional difficulties. The qualitative results showed that the students had reached a quite satisfactory level of well-being, 13 years after the tsunami. The children had attended psycho-social education awareness programs and received psycho-social “training” and counselling interventions. These were implemented in order to successfully develop the students’ well-being. The findings suggested that the students required further professional counselling services and welfare facilities within the school system and also a drug prevention program in order to further their well-being, based on a long-term plan.